Preschool teacher’s preparation time - Hreinsdóttir, Anna Magnea; Karlsdóttir, Kristín; Björnsdóttir, Margrét Sigríður; Ólafsdóttir, Sara M. (Menntavísindasvið Háskóla Íslands, 2022)
The aim of the study was to explore how preschools organize teacher’s preparation time and how they prioritize the tasks carried out. The purpose was to see the impact preparation time has on the teacher’s professionalism and the quality of children’s play, learning and communication in the preschools. The article describes a study carried out within the Centre for Research in Early Childhood Education at the University of Iceland for the purpose of following up on a recent change in wage agreements Iceland in 2021 where preschool teachers’ time for planning, preparation and assessment was considerably increased. According to these agreements, preschool teachers have from 7 – 10 hours each week for their preparation. The study seeks support from research and theories on teachers’ professionalism, the quality of preschool activities and ideas about learning communities in schools, where preschool teachers collaborate and learn from each other. In this article, the focus is on answering two research questions: How is preparation time arranged and what are the priorities of projects carried out during preparation? Eight preschools were purposely selected to be represented in the study and the data mainly builds on interviews with one preschool leader, one department head and one preschool teacher in each of the schools: a total of 24 participants. The interviewees were asked to describe how preparation time was organized; what time of day preparation was carried out, how tasks were prioritized and what resources were available to preschool teachers in their preparation. The results reveal preschool teachers’ general satisfaction with having increased time for preparing their work with the children. Nevertheless, diverse opinions appeared towards the way criteria for the preparation time were allocated to preschools. To some extent, the data is influenced by the way preparation time is planned in primary schools, possibly related to the importance of making pre-school teachers’ working hours comparable to those of ...